Molecular Docking Based Screening of Plant Flavonoids as Dengue NS1 Inhibitors - Qamar, Muhammad Tahir ul (Biomedical Informatics, 2014)
Dengue infection has turned into a serious health concern globally due to its high morbidity rate and a high possibility of increase in its mortality rate on the account of unavailability of any proper treatment for severe dengue infection. The situation demands an urgent development of efficient and practicable treatment to deal with Dengue virus (DENV). Flavonoids, a class of phytochemicals present in medicinal plants, possess anti-viral activity and can be strong drug candidates against viruses. NS1 glycoprotein of Dengue virus is involved in its RNA replication and can be a strong target for screening of drugs against this virus. Current study focuses on the identification of flavonoids which can block Asn-130 glycosylation site of Dengue virus NS1 to inhibit viral replication as glycosylation of NS1 is required for its biological functioning. Molecular docking approach was used in this study and the results revealed that flavonoids have strong potential interactions with active site of NS1. Six flavonoids (Deoxycalyxin A; 3,5,7,3',4'-pentahydroxyflavonol-3-O-beta-D-galactopyranoside; (3R)-3',8-Dihydroxyvestitol; Sanggenon O; Epigallocatechin gallate; Chamaejasmin) blocked the Asn-130 glycosylation site of NS1 and could be able to inhibit the viral replication. It can be concluded from this study that these flavonoids could serve as antiviral drugs for dengue infections. Further in-vitro analyses are required to confirm their efficacy and to evaluate their drug potency.